Peningkatan Mutu Dikalangan Guru SD Gugus Diponegoro Kecamatan Ungaran Barat dengan Kemampuan Penyusunan Proposal PTK Melalui Workshop - Ardi Surya Satria Ridwan (UHN IGB Sugriwa Denpasar, 2017)
The purpose of this study was to analyze the quality improvement activities to draw up action research through workshops among primary school teachers in Gugus Diponegoro Kecamatan Ungaran Barat. This research is an action research descriptive and qualitative approach. Although the results are still far from PTK relevance proposal but interest to make a PTK proposal increases. In PTK workshop proposal process, there were many problems faced by the teachers who have difficulty in using computers and many teachers do not participate actively. The conclusion shows the actions taken to improve the ability of teachers through workshops PTK proposal showed success in developing a PTK proposal.